염소·이산화염소 및 오존에 의한 藻類의 멸살효과에 대하여 : 상수중 오염된 조류를 중심으로 - 차영호 (연세대학교 보건대학원, 1988)
[한글] 현재 상수처리시 소독제로 사용하고 있는 염소는 상수에 오염되어 정수처리효과를 저하시키며 물의 맛과 냄새의 원인인 조류에 대하여는 완전한 사멸효과를 기대할 수가 없다. 조류의 과다성장은 정수처리시 여과지에 조류막을 형성하여 여과지 및 배관을 막아 상수처리기능을 저하시킨다. 염소처리시 생성되는 수중의 잔류염소는 유기물질과 반응하여 발암성물질인 THM(trihalomethane)등의 인체에 유해한 화합물질을 생성하는 커다란 단점이 있다. 이에 염소이외에 대체소독제로 이용되고 있는 이산화염소, 오존을 적용하여 각 소독제의 조류멸살효과와 각종 소독제들의 농도변화, 접촉시간 경과 및 복합투입에 따른 조 류멸살효과를 비교 측정하여 보았다. 실험방법은 상수원 및 수도수에서 분류한 조류를 접종한 후 염소, 이산화염소, 오존을 각각 0.2㎎/ℓ, 0.5㎎/ℓ, 0.5㎎/ℓ, 1.0㎎/ℓ, 10.0㎎/ℓ의 농도로 투입한 후 10㎎/ℓ씩을 취하여 조류배양액에 접종하고 조도 400O±400lux, 온도20±1℃를 유지하면서 6일간 배양하였다. 매일 1∼2 ㎖의 배양액을 취하여 spectrophotometer의 700nm에서 흡광도의 변화를 측정하여 증식율을 구하였다. 본 실험에서 얻어진 결과는 다음과 같다. 1. 상수원수(정수장 유입수)의 현존 상수처리과정 중 적용되고 있는 염소주입처리에 의해서는 조류의 완전한 제거가 이루어지지 않고 있었으며 수도수에서는 Anabena sp., Fragilaria sp.등이 출현되었다. 2. 염소 단독투입의 경우 10.O㎎/ℓ의 농도로 1시간, 2시간, 5시간, 24시간 접촉 후 6일 배양에 따른 조류증식율은 대조군이 146.0%인 반면 74.0%, 68.0%, 48.0%, 36.0%로 각각 증식이 억제되었다.. 3. 이산화염소의 경우 10.0㎎/ℓ의 농도로 1시간, 2시간, 5시간, 24시간 접촉후 6일배양에 따른 조류증식율은 대조군이 146.0%인 반면 64.0%, 56.0%, 52.0%, 35.1%로 각각 중식이 억제되었다. 또한 염소단독투입군 보다는 양호한 증식억제를 보여주었다. 4. 오존외 경우 10.O㎎/ℓ의 농도로 1시간, 2시간, 5시간, 24시간 접촉후 6일 배양에 따른 조류증식율은 대조군이 146.0%인 반면 15.6%, 11.3%, 7.6%, 5.0%로 각각 증식이 억제되었다. 또한 오존 단독투입군은 염소 및 이산화염소 단독투입군보다 양호한 증식억제 를 보여 주었다. 5 .복합투입의 경우 농도변화(0.2, 0.5, 1.O㎎/ℓ)와 동시에 순차투입하였을때 동일농도(1.0㎎/ℓ)에서의 증식율을 비교하여 보면 대조군의 증식율이 146.0%인데 비하여 염소투입 후 이산화염소투입의 6일후 조류 증식율은 36.0%였다. 또한 염소투입후 오존투입, 이산화염소투입후 오존투입, 오존투입 후 이산화염소투입에 따른 조류증식율은 각각 36.7%, 31.6%, 22.8%로 대조군에 비하여 뚜렷한 성장의 감소를 볼 수 있었다. 6. 단독 및 복합투입의 경우 농도의 증가와 접촉시간 증가에 따라 조류의 증식율은 억제됨을 알 수 있었다. 이상의 결과로 보아 단독투입의 경우 상수 소독제의 조류멸살효과는 오존>이산화염소>염소의 순이었으며 앞으로 복합투여를 실시할 경우 경제성 및 실제 적용가능성을 고려한 소독방법의 경우는, 염소투입후, 이산화염소처리나, 염소투입후 오존의 복합투입이 효과적이라고 생각된다. [영문] While the chlorine has been used as one of the major disinfectants of the drinking water supply system, it is not effective to distroy the polluted algae with the practical concentration in drinking water treatment. Overgrow of algae forms membraneous block in the filter bed whereby closing the filteration plants and pipeline. This results in weakening the efficiency of drinking water supply system. In chlorine treatment, the residual chlorine in drinking water reacts with organic materials(humic substances), and produce THMs(trihalomethanes) which is known as carcinogenic substance. Recently, chlorine dioxide and ozone have been used for disinfection of microorganisms as an alternative to chlorine disinfactant. In the experiment, sample of drinking water was mixed with algae, and then the chlorine, chlorine dioxide and ozone were added to the testing vessels at the concentration of 0.2㎎/1, o.5㎎/1, 1.O㎎/1, 10.O㎎/1. From this mixed materials in the vessel, a sample of 10㎖ was again extracted to fed into the algae cultured media and incubated for six days with luminous density at 4000±400 lux and temperature at 20±1℃. To estimate the growth rate of algae, changes in optical density were measured at the 700nm in a spectrophotometer using 1-2㎖ of cultured solution from the sample. The results were summarized as follows: 1. The existing treatment of water supply, with chlorine treatment was not effective to the removal of algae. Species of Anabena and Fragilaria were detected in the drinking tap water. 2. When chlorine treatment was used only, It was contacted in 1hr, 2hrs, 5hrs, 24hrs with concentrations of 10.O㎎/1 and cultured in incubator for 6 days, the control algal growth rate was 146.0%, whereas chlorine contacted algal growth rates were limited to 78%, 68%, 48% and 36%. 3. When chlorine dioxide treatment was used only, contacted in 1hr, 2hrs, 5hrs, 24hrs with concentration of 10.0㎎/1 and then cultured in incubator for 6 days the control algal growth rate were limited to 64%, 56%, 52%, 35.1%. 4. When ozone treatment was used only, it was contacted in 1hr, 2hrs, 5hrs, 24hrs with concentrations of 10.0㎎/l and then cultured in incubator for 6 days, the control algal growth rate were grown about 146.0%, in contrast to ozone contacted algal growth rate were limited to 15.6%, 11.3%, 7.6%, 5.0%. 5. In the cases of combined treatments of disinfectants, the control algal growth rate were demonstrated about 146.0%, and then in the order of injection with the chlorine and chlorine dioxide contacted algal growth rates were demonstrated as about 36.0%. Each algal growth rates of the treatment of sample, the chlorine dioxide contact sample, were limited to 36.7%, 31.6%, 22.8%. 6. In the case of single or combined treatments, the algal growth rates were inhibited by increases of concentration and prolongation of contact time. From these results, disinfection effects of single treatment were in the order of Ozone, Chroline dioxide and chlorine. However, the combined treatments tested In this study were found to be more effective then the above single treatments.
환경관리학과/석사